Content marketing and social media marketing as predictors of OZ Radio Bali brand awareness - Ni Kadek Dwi Sri Rahayu; Nyoman Indah Kusuma Dewi; Ni Putu Maha Lina (Priviet Social Sciences Journal, 2026)
This inquiry provides an empirical assessment regarding how content marketing and social media marketing predict the brand awareness of OZ Radio Bali, particularly as contemporary youth audiences increasingly pivot toward digital alternatives. Operating within a quantitative cross-sectional explanatory survey design, this study focused on a population consisting of active TikTok followers of OZ Radio Bali. Utilizing Cochran's formulation alongside a convenience sampling approach, a total of 96 respondents were selected. Primary data gathered through validated online instruments using a Likert-scale design were subsequently evaluated via multiple linear regression analyses implemented within the SPSS environment. The derived statistical metrics reveal that, on a partial basis, content marketing (t = 9.303; p < 0.001) and social media marketing (t = 8.307; p < 0.001) are positively and significantly associated with brand awareness. When evaluated simultaneously, these joint independent predictors establish a significant relationship with brand awareness (F = 130.114; p < 0.001). Furthermore, an R² value of 0.737 demonstrates that this specific regression framework successfully explains 73.7% of the total variance observed in brand awareness, whereas the residual 26.3% stems from unobserved exogenous factors. Ultimately, cultivating a deliberate operational harmony between relevant audio-visual production and responsive digital community interactions remains paramount to preserving institutional visibility within the current media convergence landscape. Keywords: content marketing; social media; brand awareness; radio